The apoptotic effect of a high dose of toluene on liver tissue during the acute phase: an experimental study - Ayan, Murat; Tas, Ufuk; Sogut, Erkan; Kuloglu, Tuncay; Cayli, Sevil; Kocaman, Nevin; Sahin, Mehmet (Sage Publications Inc, 2013)
The aim of this study is to investigate the acute toxic effects of high-dose toluene and its mechanisms on the liver tissue of toluene-treated rats. In this study, 16 adult male Wistar albino rats (200-220g) were divided into two equal groups. Group I was used as a control group, while group II was exposed to high dose of toluene, 5200mg/kg (6ml/kg per gavage). After the 3-hour experimental period, blood samples and liver tissues were taken from the euthanized animals. Serum aspartate and alanine aminotransferase levels were assayed. Liver tissues were fixed in 10% neutral formalin, then embedded in paraffin and sectioned (5 m thickness). Sections were stained with hematoxylin and eosin for histopathological examination. A terminal transferase dUTP nick end labeling assay was also done for the determination of apoptosis in liver tissues. For the determination of Bax and caspase-3 immunoreactivity, the sections were stained using avidin-biotin-peroxidase immunohistochemical method. The level of plasma transaminase was found to be increased in toluene administered rats. Additionally, slight degeneration of hepatocyte and mononuclear cell infiltration was observed in the liver tissue sections and a high (+++) immunoreactivity for Bax and caspase-3 protein was observed in the toluene group. This study showed that the high dose of toluene triggers apoptosis in the liver of rats via the mitochondrial pathway in acute period.
Keywords: Toluene; apoptosis; liver tissue; immunohistochemistry; rat